2015
DOI: 10.1021/acs.bioconjchem.5b00572
|View full text |Cite
|
Sign up to set email alerts
|

p-SCN-Bn-HOPO: A Superior Bifunctional Chelator for 89Zr ImmunoPET

Abstract: Zirconium-89 has an ideal half-life for use in antibody-based PET imaging; however, when used with the chelator DFO, there is an accumulation of radioactivity in the bone, suggesting that the 89Zr4+ cation is being released in vivo. Therefore, a more robust chelator for 89Zr could reduce the in vivo release and the dose to nontarget tissues. Evaluation of the ligand 3,4,3-(LI-1,2-HOPO) demonstrated efficient binding of 89Zr4+ and high stability; therefore, we developed a bifunctional derivative, p-SCN-Bn-HOPO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
144
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(152 citation statements)
references
References 44 publications
(105 reference statements)
8
144
0
Order By: Relevance
“…When loosely chelated, 89 Zr is known to be a bone seeker (17). Indeed, evidence suggests that when 89 Zr is chelated to antibodies with desferrioxamine, radioactivity accumulates in the bone (18). Thus, non-specific binding of potentially free 89 Zr at sites of osseous turnover associated with bone metastases could be the reason for the false positive osseous foci in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When loosely chelated, 89 Zr is known to be a bone seeker (17). Indeed, evidence suggests that when 89 Zr is chelated to antibodies with desferrioxamine, radioactivity accumulates in the bone (18). Thus, non-specific binding of potentially free 89 Zr at sites of osseous turnover associated with bone metastases could be the reason for the false positive osseous foci in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When loosely chelated, 89 Zr is known to be a bone seeker [11]. Indeed, evidence suggests that when 89 Zr is chelated to antibodies with desferrioxamine, radioactivity accumulates in the bone [12]. Thus, non-specific binding of potentially free 89 Zr at sites of osseous turnover associated with bone metastases could result in false-positive osseous foci.…”
Section: Discussionmentioning
confidence: 99%
“…Although the resulting slightly impaired stability of 89 Zr-DFO-mAb does not really hamper image quality, it is clear from preclinical studies that in time, some 89 Zr 4+ becomes released from the conjugate and accumulates in the bones [1316]. For example, Perk et al compared the biodistribution of the conjugates 89 Zr-DFO-cetuximab, 88 Y-DOTA-cetuximab and 177 Lu-DOTA-cetuximab in tumor-bearing nude mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some chelators contain hydroxamate moieties, like the linear and macrocyclic tetrahydroxamate chelators reported by Guerard et al, and the trihydroxamate chelators reported by Boros et al and Zhai et al [17–20]. Other examples do not contain hydroxamate moieties like p -SCN-Bn-H6phospha, 3,4,3-(LI-1,2-HOPO), and 3-hydroxypyridin-2-one (2,3-HOPO) [16, 2123]. However, none of these developments have led to a bifunctional chelator that outperforms 89 Zr-DFO-mAb complexes on all abovementioned aspects of an optimal chelating agent.…”
Section: Introductionmentioning
confidence: 99%